Features of structural and functional heart remodeling in patients with arterial hypertension and thyrotoxicosis depending on the degree of its compensation - Korchagina, Daria (ScienceRise: Medical Science, 2020)
The aim: to study the peculiarities of structural and functional remodeling of the heart in arterial hypertension patients depending on the degree of thyrotoxicosis compensation. Materials and methods. The study included 80 patients with AH, 50 patients per AH with concomitant TT (mean age 52.6±12.7 years, mean duration of AG – 6.5±4.0 years, duration of TT 3.9±2.5), depending on the degree of compensation for TT the patients were divided into 2 groups (group 1 – compensated TT, group 2 – decompensated TT). The control group consisted of 30 patients from AH (mean age – 56.2±7.6 years, mean duration of AG – 8.8±4.4 years), who had excluded thyroid dysfunction during the examination. Results and discussion. According to the results of echocardiography, types of myocardial hypertrophy of the left ventricle were studied. Correlation and regression analyses were performed concerning the influence of thyroid hormone on the systolic blood pressure level according to the data of the outpatient blood pressure monitor. Conclusions. It was proved that the absence of thyrotoxicosis compensation in patients with arterial hypertension is accompanied by an increased level of systolic blood pressure, both during the whole day and during the day and night periods as compared to the control group and the group of patients with compensated thyrotoxicosis. Feedback between the systolic blood pressure level and the thyroid hormone has been proved. Based on correlation and regression analyses, it was established that heart remodeling in patients with arterial hypertension and thyrotoxicosis depends both on the level of systolic blood pressure (according to outpatient blood pressure monitoring) and the level of thyroid hormone